Views of surgical nurses on factors influencing post-operative pain level assessment in surgical wards at the selected public hospital in Gauteng Province - Rasweswe, Melitah M. (University of Pretoria, 2023)
Dissertation (MCur (Advanced Perioperative Nursing Science))--University of Pretoria, 2023.